Thrombospondin-1 suppresses wound healing and granulation tissue formation in the skin of transgenic mice - Streit, Michael (Oxford University Press, 2000)
The function of the endogenous angiogenesis inhibitor thrombospondin-1 (TSP-1) in tissue repair has remained controversial. We established transgenic mice with targeted overexpression of TSP-1 in the skin, using a keratin 14 expression cassette. TSP-1 transgenic mice were healthy and fertile, and did not show any major abnormalities of normal skin vascularity, cutaneous vascular architecture, or microvascular permeability. However, healing of full-thickness skin wounds was greatly delayed in TSP-1 transgenic mice and was associated with reduced granulation tissue formation and highly diminished wound angiogenesis. Moreover, TSP-1 potently inhibited fibroblast migration in vivo and in vitro. These findings demonstrate that TSP-1 preferentially interfered with wound healing-associated angiogenesis, rather than with the angiogenesis associated with normal development and skin homeostasis, and suggest that therapeutic application of angiogenesis inhibitors might potentially be associated with impaired wound vascularization and tissue repair.